Click on Click: Click-Flavone Glycosides Encapsulated in Click-Functionalised Polymersomes for Glioblastoma Therapy - Nuno M. Saraiva; Ana Alves; Ana Isabel Barbosa; Andreia Marinho; Salette Reis; Marta Correia-da-Silva; Paulo C. Costa (Pharmaceutics)
In this study, three new 3,7-dihydroxyflavone (1) derivatives with different sugars were designed and synthesised by click chemistry. Click chemistry requires the previously modification of building blocks with azide and alkyne groups and therefore, the 3,7-dihydroxyflavone (1) was first converted in 3,7-(prop-2-yn-yloxy)flavone (2) and acetobromo-α-D-glucose (3) was converted into 2,3,4,6-tetra-O-acetyl-β-glucopyranosyl azide (4). Subsequently, a click reaction was performed via copper-catalysed cycloaddition (CuAAC) between 2 and 4, as well as between 2 and 2-acetamido-3,4,6-tetra-O-acetyl-2-deoxy-β-D-glucopyranosyl (AG931) and, 2 and commercial 2-azidoethyl 2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl (AG358), resulting in three distinct disubstituted flavone glycosides (5a–5c). Biological assays performed on L929 fibroblast cell lines and human glioblastoma astrocytoma U-251 cell lines indicated cytocompatibility with fibroblasts and reduced metabolic activity of GBM cells in the presence of compound 5b and 5c. To enhance therapeutic effect, improve local drug delivery, and overcome solubility issues of these high molecular weight compounds, the synthesised compounds were encapsulated in polymeric particles (polymersomes, PMs) composed of polylactic acid-polyethylene glycol (PEG-PLA) functionalized, once more by click chemistry, with 0.1 mol% transferrin mimetic (T7—HRPYIAH) peptide. The PMs were prepared by solvent displacement and exhibited stability over 100 days, encapsulation efficiency of 39–93%, and mean size diameters of 120–180 nm. The toxicity assays of the PMs on the U-251 cell line showed a significant decrease in metabolic activity, supporting the potential of this delivery system against GBM. Among the PMs tested, the flavone 5c-based PM demonstrated the highest efficacy.